Nurr1 Modulation Mediates Neuroprotective Effects of Statins. Issue 18 (30th April 2022) - Willems, Sabine; Marschner, Julian A.; Kilu, Whitney; Faudone, Giuseppe; Busch, Romy; Duensing‐Kropp, Silke; Heering, Jan; Merk, Daniel
Abstract: The ligand‐sensing transcription factor Nurr1 emerges as a promising therapeutic target for neurodegenerative pathologies but Nurr1 ligands for functional studies and therapeutic validation are lacking. Here pronounced Nurr1 modulation by statins for which clinically relevant neuroprotective effects are demonstrated, is reported. Several statins directly affect Nurr1 activity in cellular and cell‐free settings with low micromolar to sub‐micromolar potencies. Simvastatin as example exhibits anti‐inflammatory effects in astrocytes, which are abrogated by Nurr1 knockdown. Differential gene expression analysis in native and Nurr1‐silenced cells reveals strong proinflammatory effects of Nurr1 knockdown while simvastatin treatment induces several neuroprotective mechanisms via Nurr1 involving changes in inflammatory, metabolic and cell cycle gene expression. Further in vitro evaluation confirms reduced inflammatory response, improved glucose metabolism, and cell cycle inhibition of simvastatin‐treated neuronal cells. These findings suggest Nurr1 involvement in the well‐documented but mechanistically elusive neuroprotection by statins. Abstract : Simvastatin modulates Nurr1 activity and alters the expression of genes involved in inflammation, glucose metabolism, and cell cycle regulation in astrocytes in a Nurr1 dependent fashion. In consequence, simvastatin‐treated astrocytes display a reduced inflammatory response, enhanced glucose consumption, and lower cell cycle activity. Nurr1‐mediated effects may hence importantly contribute to neuroprotection by simvastatin.